The Effectiveness of Augmented Reality Historical Site Learning on Students’ Digital Literacy and Learning Motivation: An Experimental Study - Nur Qodriah Syafitri; Nur Afina Inaya Devi; Ince Nisa’ul Khumairah Shaleh; Alfian Jimran; Hamriani; Alma Paramita (Information Technology Education Journal, 2024)
This study investigates the effectiveness of Augmented Reality (AR) historical sites in enhancing digital literacy and learning motivation among secondary school students. Despite the increasing integration of technology in education, the impact of AR on students’ engagement with history content and their ability to navigate digital tools remains underexplored. This research addresses this gap by examining how AR-based interventions support meaningful learning and promote interest in history. An experimental study was conducted with 120 secondary school students divided into control and experimental groups. The experimental group engaged with AR historical sites through mobile and tablet applications, combined with interactive timelines, while the control group used traditional learning methods. Pre- and post-tests measured digital literacy and learning motivation, and questionnaires assessed user experience and engagement. Statistical analyses, including paired t-tests and ANCOVA, were performed to evaluate differences between groups. The results indicate that students in the AR-based learning group showed a significant increase in digital literacy scores (mean increase = 18%, p < 0.01) and learning motivation (mean increase = 21%, p < 0.01) compared to the control group. Students reported higher engagement and improved ability to navigate and interpret historical content through AR visualizations and interactive timelines. This study demonstrates the potential of AR for history education, suggesting that immersive technologies can strengthen both content understanding and digital competencies. Limitations include the study’s short intervention period and single-school sample, limiting generalizability. The study contributes empirical evidence supporting AR integration in history classrooms, highlighting its role in fostering digital literacy and motivation. Future research may explore longitudinal impacts, scalability across diverse curricula, and integration with collaborative learning strategies.